2018
DOI: 10.1103/physreva.97.052131
|View full text |Cite
|
Sign up to set email alerts
|

Normalization approach for scattering modes in classical and quantum electrodynamics

Abstract: We propose a novel scheme to normalize scattering modes of the electromagnetic field. By relying on analytical solutions for Maxwell's equations in the homogenous medium outside the scatterer, we derive normalization conditions that only depend on the electromagnetic field on the surface of a sphere containing the scatterer. We pay special attention to the important cases of plane wave illumination and illumination with a multipolar field, for which an explicit and easy to use normalization condition is derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 82 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…• Calculate the light-matter coupling constant from the properly normalized field strength (according to [64]), the cavity parameters and the emitter's transition dipole moment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Calculate the light-matter coupling constant from the properly normalized field strength (according to [64]), the cavity parameters and the emitter's transition dipole moment.…”
Section: Discussionmentioning
confidence: 99%
“…For the rest of this work we drop the mode index k from ω k , making the dispersion relation implicit. The electromagnetic field modes are of the form [64] …”
Section: The Cavitymentioning
confidence: 99%
“…(ω, |x| > R) = b ∈ R. This last condition guarantees the existence of a set of normalizable and orthogonal scattering modes [7]. In the Coulomb gauge and in the absence of external charges, the classical Lagrangian of such a system can be written as…”
Section: Quantization Proceduresmentioning
confidence: 99%
“…it satisfies Silver-Müller radiation conditions. In [7] it is demonstrated that the scattering modes are complete, orthogonal and normalized with respect to the scalar product…”
Section: Quantization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation